The 1989 revolution in East Germany and its impact on Unified Germany's constitutional law : the forgotten revolution? - Jaggi, Stephan (Hart Publishing, 2016)
Intergenerational synthesis as an analytical tool -- Analyzing the 1989 revolution -- Transfer of revolutionary achievements to unified Germany -- Integrating revolutionary achievements into unified Germany's Constitutional order